The relationship between social support and level of anxiety post recovery from COVID-19 - Anifa Handayani (Psycho Holistic, 2024)
Self-isolation on pandemic or activity restriction makes the social support’s level that accepted by society has decreased. People become individualism and avoid each other. People whose infected by COVID-19 often ostracized by the citizen because they are afraid of being infected. This study aim to see the correlation of social support and anxiety levels after recovering from COVID-19. There are 62 participants were got from purposive sampling technique. The result showed a negative correlation r = -0.748, where the higher the social support, the lower the level of stress experienced by the individual.